Information systems in healthcare: potential of mobile systems. The case of INEM - Fernandes, Silvia Brito (2013)
The information systems are an asset in the capacity of institutions to improve their business. As the potential of mobile systems is increasing, especially in healthcare, it is diagnosed the information system of INEM (National Institute for Medical Emergency) in some of its weaknesses and changes. In the case of human lives, which require speed and quality of care in a specific context and location, it is essential that healthcare institutions implement mobile and context-aware systems in order to prevent gaps in care since the first contact with the patient. This paper shows a system’s architecture, provided by the technical and functional development department of a company (Algardata) for context-oriented systems in dynamic environments. The aim is, whenever the patient changes his location, to immediately discover the services that best fit his needs and determine the resources required, including the position of professionals who are on duty nearby.